Statistics as a catalyst to learning by scientific method part I-an example. - P. Box, George E. (Journal of Quality Technology)
Innovation in the design and manufacture of processes and products usually comes about as a result of careful investigation-a direct process of sequential learning. Many practitioners, although familiar with "one-shot" statistical procedures, have little knowledge of the power of statistical techniques designed to catalyze investigation itself. A simple means of demonstrating and experiencing this learning process is illustrated using response surface methods to find an improved design for a paper helicopter.